Studies on nutritional composition of quality protein and normal maize (Zea mays) genotypes - K. LAKSHMI PRASANNA,; K. KESHAVULU,; M. SREEDHAR,; K. JHANSI RANI,; M.R. SUDHARSAN,; PRAKASH BABU, (Seed Research, 2026)
Chemical composition of quality protein maize (Zea mays L.) (QPM) was compared with that of normal maize genotypes. Study on nutritional traits indicated that protein and oil content were of higher magnitude in normal maize genotypes compared to QPM genotypes. However, protein quality was superior in case of QPM. Quality protein maize genotypes exhibited nearly two-fold increase in lysine and tryptophan content. In addition to that they had higher starch and fiber content compared to normal maize genotypes. The QPM genotypes viz. BQPML 5280 and BQPML 5175 were superior in nutritional parameters estimated for both quality and quantity. The normal maize lines, BML 40410 and BML 7 exhibited superior nutritional quality compared to other genotypes. The seed yield/plant showed significant positive correlation only with cob length and number of rows/cob, out of 9 yield-attributing traits. Starch and protein content of seed were negatively correlated, whereas oil and protein content were positively correlated. Seed protein content was negatively correlated with tryptophan and lysine.